The five books of Moses a reexamination of the modern theory that the Pentateuch is a late compilation from diverse and conflicting sources by authors and editors whose identity is completely unknown. - Allis, Oswald Thompson, 1880-1973 (Nutley, NJ Presbyterian and Reformed, 1964)
Includes bibliographical references and indexes
Keywords: Bible. O.T. Pentateuch -- criticism, interpretation, etc